Screening of endemic wild Vigna accessions for resistance to three bruchid species. (September 2021) - Aidbhavi, Revanasidda; Pratap, Aditya; Verma, Prasoon; Lamichaney, Amrit; Bandi, Sanjay M.; Nitesh, S.D.; Akram, Mohd; Rathore, Meenal; Singh, Bansa; Singh, Narendra P.
Abstract: Several bruchid species attack stored pulses including those belonging to Vigna species.Wild Vigna accessions offer a host of useful traits for improvement of their cultivated types and hence 42 endemic wild Vigna accessions from 13 species were screened against three cosmopolitan bruchid species viz., Callosobruchus maculatus (F.), C. chinensis L. and C. analis (F.). The accessions exhibited varied reactions to three bruchid species and were categorized based on two criteria-seed damage (SD) and susceptibility index (SI). Based on SD, IC251442 accession of V. umbellata was found highly resistant, whereas accessions of V. umbellata (IC251439, PRR 2007-2 and IC251440), V. vexillata (IC248326 and IC248343), V. trilobata (JAP10-5) and V. trineriva var. bournei (IC247407) were found resistant to C. maculatus. Likewise, the accessions of V. mungo var. mungo (IC251390, IC251385 and IC251387), V. vexillata (IC248326) and V. khandalensis (Kumur local) were found highly resistant, whereas the accessions V. umbell ata (IC251440), V. mungo var. mungo (IC251397), V. vexillata (IC248343) and V. dalzelliana (IC247408) were found resistant to C. chinensis . Interestingly, none of the accessions was found either highly resistant/resistant to C. analis. Based on SI, several accessions (including those susceptible on the basis of SD) recorded lower SI (<0.05) and were found resistant. A few accessions namely, V. trinervia (JAP 10–51), V. trinervia var. bournei (IC247407), V. pilosa (IC210575, IC210580 and IC210576) and V. dalzelliana (IC203864) were found resistant/moderately resistant to C. chinensis and C. maculatus, whereas the same lines were found moderately susceptible/susceptible against C. analis. The remaining accessions were found to be susceptible/highly susceptible to all bruchid species tested. These resistant lines could be further subjected to biochemical as well as molecular analysis to identify the specific seed components imparting resistance to bruchids. Simultaneously, these may be deployed in introgression breeding to develop bruchid resistant superior cultivars. Graphical abstract: Image 1 Highlights: Wild Vigna accessions were screened for resistance reaction to bruchid species. Seed qualitative and quantitative parameters did not influence bruchids oviposition on different accessions. Accessions belonging to five Vigna species were found resistant to C. maculatus and C. chinensis . None of the accessions were found to be resistant to C. analis.